Dilema Gender dalam Administrasi Publik - Ambar Widaningrum (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1999)
The thesis of this paper is that the images of administrative quality that characterized defenses of administrative power contains dilemmas of gender. The intellectual assumptions, definitions of knowledge, and values that shape administrative thinking, and in turn the conditions of people's live are likely to remain as masculine. In either case, if the structural nature of public administration is still based on the culturally masculine qualities, advancing equal opportunity and action for both women and men, cannot be counted on in and of themselves to change the tenor of public administrative affairs.